Where Is Bacosine in Commercially Available Bacopa monnieri? - Ritter, Stefanie; Urmann, Corinna; Herzog, Rainer; Glaser, Jan; Bieringer, Sebastian; Geisberger, Thomas; Eisenreich, Wolfgang; Riepl, Herbert (Planta Medica, 2020)
Bacopa monnieri is an Ayurvedic plant with rising interest in the pharmacological effects of its extract and constituents, including flavonoids, saponins, and triterpenes such as cucurbitacins, betulinic acid, and bacosine. The latter two compounds are isomeric 3-hydroxy lupenoic acids, which vary only in the arrangement of the carboxylic acid group and the methyl group at C-27 and C-28 and the orientation of the hydroxy group at C-3. In this study, we have reinvestigated the contents of betulinic acid and bacosine, respectively, in extracts from various commercially available B. monnieri powders and food supplements. To our surprise, HPLC-ion trap time-of-flight analyses identified only betulinic acid, but not bacosine, in all extracts under study, which was verified by GC-MS, HPLC-ELSD, 1D NMR (1H,13C), and 2D NMR (1H,1H COSY, 1H,13C HMBC, 1H,13C HSQC, 1H,1H NOESY) experiments. Moreover, it turned out that commercially available reference samples of bacosine were structurally identical with betulinic acid.
Keywords: Bacopa monnieri; Plantaginaceae; Brahmi; bacosine; betulinic acid; triterpene; constitutional isomers